ELECTRONIC WAREHOUSE RECEIPTS REGISTRY AS A STEP FROM PAPER TO ELECTRONIC WAREHOUSE RECEIPTS - Kovačević, Vlado; Zakić, Vladimir; Milovanović, Miloš; Subić, Jonel; Jeločnik, Marko (Economics of Agriculture, 2016)
The aim of this paper is to determine the economic viability of the electronic warehouse receipt registry introduction, as a step toward electronic warehouse receipts. Both forms of warehouse receipt paper and electronic exist in practice, but paper warehouse receipts are more widespread. In this paper, the dematerialization process is analysed in two steps. The frst step is the dematerialization of warehouse receipt registry, with warehouse receipts still in paper form. The second step is the introduction of electronic warehouse receipts themselves. Dematerialization of warehouse receipts is more complex than that for fnancial securities, because of the individual characteristics of each warehouse receipt. As a consequence, electronic warehouse receipts are in place for only to a handful of commodities, namely cotton and a few grains. Nevertheless, the movement towards the electronic warehouse receipt, which began several decades ago with fnancial securities, is now taking hold in the agricultural sector. In this paper is analysed Serbian electronic registry, since the Serbia is frst country in EU with electronic warehouse receipts registry donated by FAO. Performed analysis shows the considerable impact of electronic warehouse receipts registry establishment on enhancing the security of the system of public warehouses, and on advancing the trade with warehouse receipt.